2021
DOI: 10.1007/s00167-021-06458-2
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal tears are more common than previously identified, however, less than a quarter of people with a tear undergo arthroscopy

Abstract: Purpose The management of meniscal tears is a widely researched and evolving field. Previous studies reporting the incidence of meniscal tears are outdated and not representative of current practice. The aim of this study was to report the current incidence of MRI confirmed meniscal tears in patients with a symptomatic knee and the current intervention rate in a large NHS trust. Methods Radiology reports from 13,358 consecutive magnetic resonance imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Secondly, many of the patients would not meet current national and international indications for surgery, as a result the existing evidence may be outdated [3,5]. Research on current UK clinical practice has found that only a quarter of patients with a meniscal tear on MRI actually undergo surgery [1]. Rather than including all patients with a meniscal tear in a study, we recommend further studies being performed with patients who meet the current indications for surgery and those listed for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, many of the patients would not meet current national and international indications for surgery, as a result the existing evidence may be outdated [3,5]. Research on current UK clinical practice has found that only a quarter of patients with a meniscal tear on MRI actually undergo surgery [1]. Rather than including all patients with a meniscal tear in a study, we recommend further studies being performed with patients who meet the current indications for surgery and those listed for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With an incidence of 222/100,000 and accounting for 70,000 hospital admissions per year, meniscal tears are a common pathology with considerable healthcare resource utilisation [1,2]. National and international guidelines have recently been published on the management of patients with a meniscal tear [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Meniscal injuries are a common diagnosis, with an estimated prevalence of 222 per 100,000 [1], often going hand-in-hand with cartilage lesions [2]. Despite advances in surgical meniscal restoration, numerous lesions remain irreparable [3], often necessitating meniscectomy [4][5][6], which can accelerate joint degeneration, leading to the development of osteoarthritis [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequently diagnosed knee injuries is meniscus tears, which can result from traumatic injury or degenerative changes due to age or overuse and cause ongoing knee pain, swelling, and stiffness, leading to a decline in functionality [ 3 , 4 ]. According to the literature, the incidence of meniscus tears is estimated to be 60–70 per 100,000 individuals per year, with a higher incidence among males in all age groups, ranging from 2.5:1 to 4:1 [ 5 ]. Moreover, in the United States, meniscus tears are the most frequent intra-articular knee injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%